Pembangunan Sistem Informasi Pengelolaan Alat Dan Bahan Praktek Pada Politeknik Pertanian Negeri Payakumbuh - camelia meli (JATISI (Jurnal Teknik Informatika dan Sistem Informasi), 2021)
The development of information technology has touched the process within the scope of the university in order to improve the effectiveness and efficiency of work. One of the examples is the management tool at State Agricultural Polytechnic of Payakumbuh which is less efficient due to applying a manual system. State Agricultural Polytechnic of Payakumbuh is Vocational education of which has the meeting of 70% practice, the equipment and material requirements are submitted every semester by the supervisor before the lecture begins. Submission the equipment and material requirements are types/materials, the number of tools/materials, used at the meeting keberapa, location/labor. By using the current manual system which is less efficient in the management requires an information system to facilitate the submission of tools and practice materials. The process of making this information system using the Method of Extreme Programming (XP). Extreme Programming (XP) is selected due to the software that will be made less complex and is classified as small software and also requires short development time. Where Stages of this method is Panning, Design, Coding, Testing. Results of the Development of Information System for Tool Management and Practice Material will be an application that will help speed up the process of submitting Tools and Practice Materials. The application is made with the programming language PHP and the database is MySQL. While for framework using CodeIgniter and Bootstrap. Keywords: Extreme Programming, PHP, MySQL, Codeigniter, Bootstrap